Perilaku Siswa dalam Proses Pembelajaran PAI di SMP Islam Darul Ulum Banda Aceh dan SMP Insyafuddin Banda Aceh - Birrul Walidain (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Student behaviors are the nature of actions possessed by students which are influenced by customs, attitudes, emotions, values, ethics, power, persuasion, and genetics. Student behaviors are grouped into reasonable behaviors, acceptable behaviors, strange behaviors, and deviant behaviors. However, what has been portrayed today in both international and local media is that there are many deviations in the student behaviors especially at the junior high school level. Therefore, the present study aimed to investigate the types of student behaviors in the learning process at school, the procedures in developing the student behaviors within the Islamic religious education learning process, and the obstacles in developing the student behaviors within the Islamic religious education learning process. The study took place at two public junior high schools, SMP Islam Darul Ulum Banda Aceh and SMP Inshafuddin Banda Aceh. The study used a descriptive method with a qualitative approach. The results of the study showed that the types of student behaviors in the learning process varied greatly. There were students who were passive and those who were active. In terms of the porcedures, is done by analyzing the needs of students. Further, the obstacles in developing the student behaviors included the lack of attention from the parents/guardians regarding changes in the student behaviors and the lack of communication between the teachers, the parents/guardians, and the Islamic education teachers.